Prevalence and risk for overweight among employees in a leading auto-mobile industry in India - Roy, Runalika; Sukumar, Gautham Melur; Kupatira, Kowshik (International Journal Of Community Medicine And Public Health, 2021)
Background: Overweight is a major risk factor for the non-communicable diseases. India is home to nearly 164 million industrial workers (2017) and yet information about prevalence and risk of overweight among them is limited. Being overweight can adversely affect a person's productivity in his workplace and increase the risk of non-communicable diseases. The objective was to assess the prevalence of overweight and association between overweight and employee age, type of work and native origin. Methods: The longitudinal analysis was conducted using periodical medical examination (PME) data of employees from 2010-2018. Relevant data were collected. Year-wise prevalence of overweight was estimated along with specific prevalence by age, type of work and region. Results: The mean weight of employees increased from 68.1 kgs to 72.6 kgs (2010-2018). Overweight proportion was significantly higher in non-production departments. Overweight prevalence ranged between 15-29.8% among Karnataka regions in 2010 in production employees but reached 35-55.6% by 2018. Significant association was found between overweight with type of work and region. Conclusions: The increase in weight over time indicates the trend of overweight and weight reduction interventions are needed in workplaces to prevent the risk of NCDs.